2015
DOI: 10.1507/endocrj.ej15-0192
|View full text |Cite
|
Sign up to set email alerts
|

Association between age at menarche and diabetes in Korean post-menopausal women: results from the Korea National Health and Nutrition Examination Survey (2007-2009)

Abstract: POST-MENOPAUSAL women are highly exposed to multiple health problems and risk of diabetes is higher in postmenopausal women than in their pre-menopausal counterparts [1]. Diabetes decrease healthrelated quality of life because of diabetic complications, and increase burden of disease [2]. Considering the fact that diabetes-caused death rate per 100,000 is 37.5 in women aged 50-69 years and 186.9 in women aged 70-80 years, whereas 2.7 in women aged 15-49 years, prevention and treatment for diabetes are an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 38 publications
4
20
1
Order By: Relevance
“…To the best of the authors’ knowledge, this is the first study to report on the association between age at menarche in patients with type 2 diabetes. It is reported that earlier‐onset menarche is associated with obesity and the development of type 2 diabetes mellitus in later life2, 3, 4, 5, 6, 7, 8, 9, 10, 11. The present results extend the association between age at menarche and obesity to patients with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…To the best of the authors’ knowledge, this is the first study to report on the association between age at menarche in patients with type 2 diabetes. It is reported that earlier‐onset menarche is associated with obesity and the development of type 2 diabetes mellitus in later life2, 3, 4, 5, 6, 7, 8, 9, 10, 11. The present results extend the association between age at menarche and obesity to patients with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 83%
“…Earlier age at menarche is associated with the future development of type 2 diabetes in Western and Asian populations4, 6, 7, 8, 9, 10, 11, and was associated with elevated HbA 1c , secondary to high BMI in the current study. These associations can be largely explained by increased adiposity.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The reference group in all analyses comprised those with an age at menarche of 12 to 13 years. There is some variation across studies in the definition of early menarche (≤10, ≤11, or ≤12 years) and late menarche (≥14, ≥15, or ≥16 years), likely influenced by the size and information available in the specific study, but our categorization is in line with commonly used cutoff values 4, 5, 6, 7, 8, 10, 11, 14, 16…”
Section: Methodsmentioning
confidence: 99%
“…Early menarche is associated with reduced insulin sensitivity and higher glucose,1, 2, 3, 4, 5, 6, 7, 8, 9 higher triglycerides and cholesterol levels,2, 6, 10 higher blood pressure,4, 5, 11, 12 and greater waist circumference and body mass index (BMI) 4, 5, 13, 14, 15. In line with these findings, there is some but less consistent evidence of an association between age at menarche and cardiovascular disease (CVD) events 12, 16, 17, 18.…”
mentioning
confidence: 99%